2018
DOI: 10.5007/1980-0037.2018v20n2p164
|View full text |Cite
|
Sign up to set email alerts
|

Repetibilidade e aplicação de testes de nado estacionário para nadadores recreacionais

Abstract: Tethered swimming tests are applied to evaluate propulsive forces in crawl stroke and may also be used to evaluate force applied by the movement of lower (leg kicking) and upper limbs (arm stroke). Considering the large number of recreational swimmers, this tool may be useful for coaches to evaluate the technique and force production by swimmers. As little attention has been paid to the application of these tests with recreational swimmers, the aims of this study were to verify the repeatability of the tethere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
0
0
Order By: Relevance
“…Dry-land strength, TF, and IMP correlated negatively with performance time in 50 m swimming, as it has previously mentioned [ 5 , 24 ]. In addition, Morouço et al [ 25 ] found similar correlations between TF and swimming velocity in short-distance tests, although the tethered swimming test was of longer duration (30 s).…”
Section: Discussionsupporting
confidence: 68%
“…Dry-land strength, TF, and IMP correlated negatively with performance time in 50 m swimming, as it has previously mentioned [ 5 , 24 ]. In addition, Morouço et al [ 25 ] found similar correlations between TF and swimming velocity in short-distance tests, although the tethered swimming test was of longer duration (30 s).…”
Section: Discussionsupporting
confidence: 68%
“…In the past years, thrust has been studied mainly using tethered swim techniques [5][6][7]. Despite the practical applications of this method and the useful data it provides, it cannot quantify for example, the force produced by each hand/foot separately during the full-body stroke [8].…”
Section: Introductionmentioning
confidence: 99%